Novel 2, 5-diketopiperazine derivatives as potent selective histone deacetylase 6 inhibitors: rational design, synthesis and antiproliferative activity - Chen, Xin; Chen, Xinyang; Steimbach, Raphael R.; Wu, Tong; Li, Hongmei; Dan, Wenjia; Shi, Peidong; Cao, Chenyu; Li, Ding; Miller, Aubry K.; Qiu, Zhixia; Gao, Jinming; et al. (European journal of medicinal chemistry, 2020)
Histone deacetylase 6 (HDAC6) has gained popular attention for its wide participation in various pathological process recently. In this paper, a series of novel derivatives containing 2, 5-diketopiperazine (DKP) skeleton were developed as potent selective HDAC6 inhibitors (sHDAC6is). Most of these compounds exhibited low nanomolar IC50 values toward HDAC6, and the best compound was 21b (IC50 = 0.73 nM) which had 144-10941-fold selectivity over other HDAC isoforms. Western blot assay further validated these compounds to be sHDAC6is. Molecular simulation of 21b was conducted to rationalize the high binding affinity for HDAC6. In the cytotoxicity experiment, 18a, 18b and 18d gave superior or comparable influence on the growth of two multiple myeloma cells U266 and RPMI-8226 compared to ACY-1215. Moreover, the combination of 18a and adriamycin showed synergistic effect against non-small cell lung cancer cell A549. 18a and 18b also demonstrated appropriate drug metabolism in human liver microsome (HLM).
Gesehen am 10.07.2024